ABILITY OF Leishmania donovani TO CONGENITAL TRANSMISSION IN EXPERIMENTAL BALB/C MICE (Basrah Journal of Veterinary Research)
The aim of the current study was to investigate the ability of the transmission of Leishmania donovani parasite from pregnant mothers to their embryos in experimental BALB/c mice. After 5 days of copulation males with females,females were injected with 1012 parasite/ml of promastigote stage through the tail vein, which is grown in NNN-medium. This study demonstrated parasite ability to congenital transmission from mothers to their embryos by placenta through the appearance of amastigote in tissue sections of liver and bone marrow of infected mice fetusescompared with uninfected fetuses. I